Preparation and Characterization of Immediate and Extended Release Levetiracetam Coated Pellets using Extrusion-Spheronization Technique : Immediate/ Extended Release Levetiracetam Coated Pellets - Paktinat, Parham; Foroutan, Seyed Mohsen; Bolourchian, Noushin (Iranian Journal of Pharmaceutical Sciences, 2025)
Levetiracetam (LEV), an antiepileptic compound with a bitter taste, is used to treat different types of epilepsy in both adult and pediatric patients. While a wide range of doses is required for various age groups, some patients have difficulties in swallowing large solid dosage forms. Therefore, this study aimed to prepare and evaluate taste-masked LEV coated pellets with immediate and extended release behavior for flexible drug dosing, ease of swallowing, and higher patient compliance. LEV core pellets were prepared using the extrusion-spheronization technique and evaluated in terms of physical properties. In the next step, two coating processes were performed separately on the optimal formulation using different polymers to prepare a taste-masked immediate release formulation and to achieve an extended release product. Further experiments were conducted on the coated pellets, such as dissolution, morphology, and taste-masking evaluations. Based on the results, optimum LEV-loaded core pellets with suitable physical properties were prepared with the size, aspect ratio, and projection sphericity of 1.18 mm, 1.08, and 0.92, respectively. Coating the pellets with Eudragit E, while having appropriate dissolution in an acidic medium, provided an acceptable taste-masking, confirmed by in-vitro and in-vivo analysis. Extended release LEV pellets were obtained by coating the core pellets with a proper Eudragit RL/RS combination. Desirable dissolution profiles were achieved using 30 % coating polymer on the surface of the pellets. In addition to the advantages of taste-masked immediate and extended release LEV pellet formulations, it should be pointed out that preparing these multi-particulate systems by coating similar core pellets with various polymers can be cost-effective from the production point of view.